2009
DOI: 10.1080/07481180903372269
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Bonds, Risk Factors for Complicated Grief, and Adjustment to Bereavement

Abstract: This study examined type of continuing bonds (CB) expression in relation to risk factors for complicated grief and measures of bereavement-related adjustment. Externalized CB expressions involving illusions and hallucinations with the deceased were distinguished from internalized CB expressions involving use of the deceased as an autonomy promoting secure base. 502 bereaved participants completed over the internet a CB measure assessing externalized and internalized CB along with various known risk-factor meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(159 citation statements)
references
References 20 publications
10
135
1
13
Order By: Relevance
“…When examining the association between internalized and externalized continuing bonds and PTG, Field and Filanosky (2010) found that internalized continuing bonds were uniquely positively associated with personal growth, a link that has been confirmed in recent studies (Scholtes & Browne, 2015).…”
Section: Intrapersonal Factorsmentioning
confidence: 60%
See 4 more Smart Citations
“…When examining the association between internalized and externalized continuing bonds and PTG, Field and Filanosky (2010) found that internalized continuing bonds were uniquely positively associated with personal growth, a link that has been confirmed in recent studies (Scholtes & Browne, 2015).…”
Section: Intrapersonal Factorsmentioning
confidence: 60%
“…This study also demonstrates the complexity within the factors by testing the associations with both forms of CB (internalized and externalized), contrary to general research on continuing bonds that focus solely on CB as a whole (Field & Filanosky, 2010).…”
Section: Strengths and Clinical Implicationsmentioning
confidence: 60%
See 3 more Smart Citations